Magnetic levitation using neodymium magnets for vertical axis wind turbine (VAWT) II - Lai, Chunji (2012)
The project, “Magnetic Levitation using Neodymium Magnets for Vertical Axis Wind Turbine” can be breakdown into 2 parts. First, the use of vertical axis wind turbine to generate energy. Secondly and also the main focus of the project, to achieve magnetic levitation using neodymium magnets. This project involved the design and fabrication of a test model vertical axis wind turbine, however as this experiment was carried out indoor without any wind condition, the author used a dc motor to simulate the wind required to spin the turbine. The advantage of this motor allows the author some control over the speed of the turbine. Achieving magnetic levitation is the ultimate goal of the project. Bearing this in mind, the author and his partner did their research and study on magnetic levitation especially on the Inductrack system. This includes the reviewing the project done by the previous project group as well as other researchers. Many ideas were discussed and some were tested out to improve the existing test model design by the previous group.